Análise da evolução da dinâmica de uma cultura de neurônios dissociados em matriz de microeletrodos usando Coerência Parcial Direcionada e Redes Complexas - Rodriguez, Mayra Mercedes Zegarra (2012)
Multi-Electrode Array, MEA, was developed more than thirty years ago. This planar device of multiple microelectrodes has been used to detect local electric potential variations created by the ion movement through the protein channels that traverses the cell membranes in the near neighborhood. MEA offers the possibility of non invasive registering of the cell and their network s activities, allowing to know how the neurons start to connect through the synapses forming a network and generating spontaneous electrophysiological activities. In order to understand the neural network dynamics in face of the spontaneous activities and its evolution in dissociated hippocampal cell cultures, important properties in the synaptic plasticity, in this work it is proposed the analysis of the evolution and modeling of the hippocampal cell cultures in MEA using the theory of Partial Directed Coherence and Complex Networks. There were used the electrophysiological records obtained using MEA60 System, of the dissociated neurons of 18 days old Wistar rat embyo, in an experiment denoted as 371, realized at the University of Genoa, Italy. As the results obtained using the Partial Directed Coherence approach, it was verified that the method is capable to detect neuronal connectivity in the neuron cultures using MEA, even with the noisy signals. It was also verified that different time delays between signals during application of the PDC method do not affect directly on the results of the causality. PDC allowed to show that in MEA the amount of direct connections resulted is less than the amount of indirect connections, through the microelectrodes. This can indicate that the neurons prefer to communicate through existing connections than creating new connections. It was also observed that it is easier to lose direct connections than indirect connections between microelectrodes through the time. Through the experiments it can be observed that the culture in 25 DIV (Days In Vitro) developed more amount of connections between neighboring electrodes, with less overall connections than the culture in 46 DIV, that had more overall connections with less neighborhood connections. Since one of the PDC features is the directionality detection between connections, it was observed direction changes through the connections through the time, even though we do not know the physiological meaning of these changes in the cognitive process. It was also observed that the established connections do not follow random patterns, showing an indicative of a free scale network, although we used small statistical measures to characterize the networks.